Survey on Daily Wages of Women, Men, And Children of the Manufacturing Industry in Santiago, Valparaíso, and Concepción in Mid-Twentieth Century Chile ¿What Can Be Done with This Information? - Casanova Brito, Mauricio; Puentes S´ánchez, Yessenia (Revista de Historia Social y de las Mentalidades, 2024)
This document transcriptions the daily wages of women and men in the manufacturing industry in Santiago and Valparaíso during mid-twentieth-century Chile. The data were published by the Yearbook of Finance and Social Funds of the General Statistical Office of Chile between 1951 and 1954. We suggest that this information may be helpful for research on a) gender gaps and b) real wages and poverty.
Keywords: Chile; Manufacturing industry; Wages; Gender gap; Child labor; Poverty